2008
DOI: 10.1515/zfwp-2008-0203
|View full text |Cite
|
Sign up to set email alerts
|

Die Höhe der sozialen Mindestsicherung – Eine Neuberechnung “bottom up” –

Abstract: The question how much money society should pay to persons without own income (i. e. the social minimum; in Germany called “Regelsatz”) has been debated extensively in Germany. A complicated procedure has been developed to derive the social minimum from the typical consumption of average lower income persons. Although the procedure as a whole is not unreasonable, it includes several standardised components which have been the cause of severe criticism and the reason for demands to raise the Regelsatz. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, this approach is highly subjective to the judgment of the experts who arrange the basket. Research by Thießen and Fischer [2008] and Hausstein [2015] on that topic enforce the issue that there is no "true need" because suggested adult benefit rates vary strongly between 132 and 734 euros per month. Hence, it is desirable to revise the Statistical Method and improve the consistency of the calculation process.…”
Section: Calculation Of Algii Standard Ratesmentioning
confidence: 99%
“…However, this approach is highly subjective to the judgment of the experts who arrange the basket. Research by Thießen and Fischer [2008] and Hausstein [2015] on that topic enforce the issue that there is no "true need" because suggested adult benefit rates vary strongly between 132 and 734 euros per month. Hence, it is desirable to revise the Statistical Method and improve the consistency of the calculation process.…”
Section: Calculation Of Algii Standard Ratesmentioning
confidence: 99%
“…In some constellations (in Europe, especially when the main earner is not well educated and many children are present in the household), the difference between full time wages from employment and SAP receipt (Lohnabstand ) is minimal (ISG, 2006) reducing incentives for work. Furthermore, there have been discussions in the public and the press about the absolute level of minimum existence, triggered by a controversial study that showed that as little as ¤132 2 but no more than ¤278 per month (excluding rent, heat and electricity payments) would be sufficient instead of the ¤347 that one would currently receive as a healthy single male SAP recipient (Thiessen and Fischer, 2008). They specifically cited that expenditure patterns for food, household items and clothing were very similar to that of the general population and in no way represented a minimum existence, but rather an average existence.…”
Section: Introductionmentioning
confidence: 99%